1981
DOI: 10.1093/brain/104.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Familial Dementia of Adult Onset With Pathological Findings of a ‘Non-Specific’ Nature

Abstract: A family is described in which 4 of 10 siblings developed a dementing illness that culminated in death within five to six years of onset. The pathological findings in 3 members were strikingly similar, and consisted of widespread nerve cell loss and astrocytosis within the cerebral cortex, status spongiosus within the outer cortical layers and, in 2, nerve cell loss and astrocytosis within the dorsomedial nucleus of the thalamus. It is concluded that the disorder described in this report does not conform preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…These include dysphagic dementias and Pick's disease [41.42], progressive thalamic and subcortical gliosis [43], Gcrtzman-Straussler disease [44][45][46], Creutzfelt-Jacob disease [47][48][49], as well as dementia associated with non specific neuropalhological features [50]. Indeed, 2 of 7 non-AD dementia cases with nonspecific neuropathological features in the present series showed a positive family history for PPD.…”
Section: Discussionmentioning
confidence: 74%
“…These include dysphagic dementias and Pick's disease [41.42], progressive thalamic and subcortical gliosis [43], Gcrtzman-Straussler disease [44][45][46], Creutzfelt-Jacob disease [47][48][49], as well as dementia associated with non specific neuropalhological features [50]. Indeed, 2 of 7 non-AD dementia cases with nonspecific neuropathological features in the present series showed a positive family history for PPD.…”
Section: Discussionmentioning
confidence: 74%
“…It was Alzheimer [30] not Pick who referred to 'ballooned cells', 'argcntophilic globes' and 'spongi cortico wasting'. Some authors simply accept circumscribed fronto-temporal atrophy without characteristic histology [31.32], Others stipulate the pres ence of ballooning of neurones in addition to the macro scopic change [33], More recently it has been proposed [15,34] that a combination of progressive dementia, lobar atrophy and neuronal argcntophilic inclusion (Pick) bodies be diagnostic of Pick's disease. Since fronto-temporal degeneration is heterogenous and can occur in a minority of cases of Alzheimer disease and CreutzfeldtJakob disease [ 12], and since ballooned neurones occur in a variety of neurodegenerative conditions [35,36], it might be suggested that the presence of Pick inclusion bodies represents the conclusive histology since they are rarely found in other conditions [37].…”
Section: Resultsmentioning
confidence: 99%
“…Such patients which represent a sub group of DFT, would presumably be excluded from FLD as pathologically defined. In both Lund and Manchester there was a high familial incidence, as in 'familial demen tia of adult onset' described by Kim et al [15] in 4 of 10 siblings of an Italian family.…”
Section: Dementia O F Frontal Lobe Typementioning
confidence: 88%
“…It was described neuropathologically and clinically in 1987-88 Gustafson, 1987;Neary et al, 1988). This entity corresponds to dementia lacking distinctive histology (Knopman et al, 1990) and to 'dementia with nonspecific pathology' (Kim et al, 1981;Clarke et al, 1986). The FTD group, according to the LundManchester consensus criteria (1994), comprises three clinico-pathological entities; Pick's disease, FLD and motor neuron disease with dementia (MNDD).…”
Section: Introductionmentioning
confidence: 99%